Atomic mass tag of bismuth‐209 for increasing the immunoassay multiplexing capacity of mass cytometry. Issue 12 (4th December 2017) - Han, Guojun; Chen, Shih‐Yu; Gonzalez, Veronica D.; Zunder, Eli R.; Fantl, Wendy J.; Nolan, Garry P.
Abstract: Mass cytometry (or CyTOF) is an atomic mass spectrometry‐based single‐cell immunoassay technology, which has provided an increasingly systematic and sophisticated view in basic biological and clinical studies. Using elemental reporters composed of stable heavy metal isotopes, more than 50 cellular parameters are measured simultaneously. However, this current multiplexing does not meet the theoretical capability of CyTOF instrumentation with 135 detectable channels, primarily due to the limitation of available chemistries for conjugating elemental mass tags to affinity reagents. To address this issue, we develop herein additional metallic mass tag based on bismuth‐209 ( 209 Bi) for efficient conjugation to monoclonal antibody. This enables the use of an addtional channel m/z = 209 of CyTOF for single‐cell immunoassays. Bismuth has nearly the same charge‐to‐radius ratio as lanthanide elements; thus, bismuth(III) cations ( 209 Bi 3+ ) could coordinate with DTPA chelators in the same geometry of O‐ and N‐donor groups as that of lanthanide. In this report, the coordination chemistry of 209 Bi 3+ with DTPA chelators and Maxpar® X8 polymers were investigated in details. Accordingly, the protocols of conjugating antibody with bismuth mass tag were provided. A method based on UV‐Vis absorbance at 280 nm of 209 Bi 3+ ‐labeling DTPA complexes was developed to evaluate the stoichiometric ratio of 209 Bi 3+ cations to the conjugated antibody. Side‐by‐side single‐cell analysis experiments with bismuth‐ and lanthanide‐tagged antibodies were carried out to compare the analytical sensitivities. The measurement accuracy of bismuth‐tagged antibody was validated within in vitro assay using primary human natural killer cells. Furthermore, bismuth‐tagged antibodies were successfully employed in cell cycle measurements and high‐dimensional phenotyping immunoassays. © 2017 International Society for Advancement of Cytometry